Legal experiences of workers: a case study from Turkey - Hatıpoğlu-Aydın, Duygu (International journal of law, crime and justice, 2021)
Focusing on people's experiences in the legal system is one way to explain the relationship between law and society. This study aims to grasp labour law and working life in Turkey from the perspectives of workers. This bottom-up qualitative research is an attempt to reveal workers' legal experiences and consciousness. Workers' narratives about their court processes concentrate on three key topics: Security, predictability, and visibility. These three perspectives reflect the expectations of workers in the legal system. Since various facts arising from workers' legal experiences compose precarious justice, which, in this study, will be discussed as the reflections of working life to the legal system.